Muravian (Eemian) deposits as an indicator of the interglacial hydrographic network of Belarus - Pavlovskaya, Irina (1998)
The paper discusses the main tendencies of relief and river network development in Belarus during the Muravian Interglacial. The study is based on regional differences of sediment types and thicknesses of Muravian Formation. Three groups of Muravian Interglacial deposits (deposits of thermokarst and ravine lakes within marginal glacial highlands, lacustrine deposits of glacial depressions and alluvial deposits) are considered in accordance with the pecularities of their distribution and structure. A study including geological drilling, palaeobotanical investigations, lithofacial analysis makes it possible to suppose that alluvial sedimentation had a subordinate role in Muravian time within the drainage basin of the Baltic Sea. Deposits of lacustrine genesis were prevalent there according to the area of distribution and to thickness. The hydrographic network of the Baltic Sea drainage basin during the Muravian Interglacial (within the territory of the Zapadnaya Dvina, Neman and Vilia basins) was different from the present one.